2017
DOI: 10.20448/2002.11.71.75
|View full text |Cite
|
Sign up to set email alerts
|

GARCH Model With Fat-Tailed Distributions and Bitcoin Exchange Rate Returns

Abstract: In the era of diminishing power from US dollar and increasing competition among world currencies, Bitcoin, as a completely new concept as a medium of exchange, has received increasing attentions over the world. Nowadays, Bitcoin also becomes an investment vehicle, which carries attractive opportunities but also significant risks for the investment community. In this paper, we have compared the empirical performance of a newly-developed heavy-tailed distribution, the normal reciprocal inverse Gaussian (NRIG), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Later, Lahmiri et al (2018) employed the FIGARCH model and found that volatility in all the Bitcoin markets considered in their study exhibits long-range dependence, while Mensi et al (2018) found that, after accounting for structural breaks, long memory in the mean and variance decreases. Among other authors who have studied the price volatility of cryptocurrencies are Chu et al (2017), Liu et al (2017), and Takaishi (2018), all of whom also used GARCH-type models, while Phillip et al (2018) employed the stochastic volatility model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Later, Lahmiri et al (2018) employed the FIGARCH model and found that volatility in all the Bitcoin markets considered in their study exhibits long-range dependence, while Mensi et al (2018) found that, after accounting for structural breaks, long memory in the mean and variance decreases. Among other authors who have studied the price volatility of cryptocurrencies are Chu et al (2017), Liu et al (2017), and Takaishi (2018), all of whom also used GARCH-type models, while Phillip et al (2018) employed the stochastic volatility model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For adequacy and parsimonious reasons, Exo − GJR − MGARCH(1, 1) and xo − GJR − DCC − MGARCH(1, 1) (Hansen and Lunde 2005;Ashley and Patterson 2010;Lim and Sek 2013). As such, based on the empirical properties of return (Cont 2001), the distributional assumption on the error vector z t is the multivariate Gaussian distribution (Liu et al 2017). The joint density is specified as follows:…”
Section: Models Identification Strategymentioning
confidence: 99%
“…The return of Bitcoin empirically exhibits leverage effect (high volatility during low return periods and low volatility during high return periods) and has evidence of return asymmetric (Bouri et al 2017a;Liu et al 2017). Therefore, since the return of Bitcoin is asymmetric and prone to leverage effect, this paper incorporates the GJR (Glosten et al 1993) asymmetric component in out GARCH model.…”
mentioning
confidence: 99%
“…Ma (2017) and Ma et al (2017) showed that the NRIG cannot outperform the Students t-distribution in modelling the metals spot return. Liu et al (2017) also suggested that the older Students t-distribution still performs better than the NRIG distribution for modelling the daily Bitcoin exchange rate returns. Additionally, some researchers suggest that the NIG and full GHD provide a better fit to some financial data than an NRIG.…”
Section: Generalised Hyperbolic Distribution and Its Subclasses In Var Estimationmentioning
confidence: 99%